THE BIOLOGICAL ASPECTS OF DOMINANT SHARKS AND RAYS LANDED IN BRONDONG FISHING PORT, LAMONGAN, EAST JAVA - Harlyan, Ledhyane Ika; Almawadah, Yulia Ainun; Lelono, Tri Djoko (Directorate of Research and Community Service (DRPM), 2021)
Shark and ray fishery issues raised in Indonesia as some species have been listed in the IUCN red list. In relation to the conservation of some shark and ray species, critical information is required related to several biological aspects to assure its fishery sustainability. This study was conducted in Brondong Fishing Port in February – March 2020. Length, weight, and maturity level data were collected from 272 shark individuals and 267 ray individuals. Several analyses were performed, such as length-weight relationship analysis, sex ratios, and maturity level analysis. The study found 18 species listed in the IUCN red list were dominantly composed of Carcharias taurus and Dasyatis kuhlii. Both species have negative allometric, while the sex ratios showed that the ratio of the number of male and female individuals for shark and ray are 1:5 and 1:2, respectively. The maturity level of male individuals for Carcharias taurus pointed that 33% full calcification (FC), 17% non-full calcification (NFC), and 50% non-calcification (NC), while for Dasyatis kuhlii resulted that 66% FC, 28% NFC, and 6% NC. It is concluded that the biological aspects of the dominant species indicated that most individuals were in a critical state, thus it is required to monitor and control their fishing pressures.